PENGARUH PENGGUNAAN CLOUD CLASSROOM (CCR) PADA MATERI IPA TERHADAP KETERAMPILAN KOMUNIKASI DAN BERPIKIR KRITIS SISWA SMP - Novita Nur Malaningtyas; Indrawati Indrawati; Iwan Wicaksono (OPTIKA: Jurnal Pendidikan Fisika, 2022)
This study aims to examine the effect of using Cloud Classroom (CCR) on science material, especially the interaction of living things with their environment on communication skills and critical thinking of junior high school students. This research is a quasi-experimental research with a post-test only control group design. The sample of this study was class VII B as the experimental class and VII C as the control class. The research instrument used was observation to measure communication skills and tests to measure critical thinking. The data obtained were analyzed using statistical tests. The results of data analysis on the observation of communication skills were not normally distributed so that it was continued using the Mann Whitney U Test, a significance value of 0.000 <0.05 was obtained, which means that there was a significant difference in the average observation of the experimental class and the control class. The results of data analysis on critical thinking were normally distributed so that the independent sample t test continued with a significance value of 0.007 <0.05, which means that there was a significant difference in the average post-test scores of critical thinking students in the experimental class and the control class. Next, the right-hand t-test was carried out and the results obtained thitung (2.837) ttabel (1.677) which means the average score of critical thinking in the experimental class is better than the control class.